Samorząd mieszkańców w obliczu wydarzeń z lat 1980 - 1983 w opiniach działaczy osiedlowych - Łajko, Elżbieta (Wydział Prawa i Administracji UAM, 1985)
In September 1983 the Group from the Faculty of Law and Administration of the University of Warsaw carried out the research on transformations in activities of residents self-government, realized within the scope of PR-5 governmental program. The research was conducted in form of panel studies. Those were repeated in the area of two housing estates (out of ten included in the previous 1977 program). We assumed that the socio political events in Poland which vividly affected individuals, social groups and the whole nation wold influence the process of experience cummulation related to the self-government in the place of residence. The analysis of statements of activists of organs of residents' selfgovernment suggests a conclusion that the post-August period of renewal became the beginning of the end of self-government in the form of the 70-ties. Structures of power previously aiding and stimulating those organs were shaken. The activists were paralysed with fear of the necessity of taking a political stand in the new situation. Animosities, and mutual accusations among activists were increasing. The self-government came under pressure of mass attacks and fostered demands of the residents who wanted to have their rights respected in the sphere of decision-making in matters of their residence location. The self-government organs were not able to get re-oriented to articulate postulates and needs arising from the ranks and to formulate them in form of definite programs of activities. The staff of self-government organs was not open to accept such social values as openess of public life, making use of mechanisms of social control, realization of the principle of government by the people. Introduction of Marshall Law in Poland resulted in a total confusion as to a possible suspension of self-government activities. Some activists openly refused to cooperate with the self government or their participation ceased. Those who remained sometimes were only obliged to it by other functions (Militiamen, voluntary reserves of the militia). The housing estates were visited by military patrols, army operational groups, commeetees of OKON and PRON whose methods were based on different principles to those adopted by the activists. The self-government organs were subordinated to those new bodies and treated it as an opportunity to regain their lost prestige Suspension and then recalling of Marshall Law in the light of empirical examination could hardly foster any more optimistic perspectives awaiting the self-government. It is presently going through difficulties resulting from a permanent lack of residents' support, reduction of staff, etc. The so called "normalization of the situation" is presently understood by the activists as the return to self-government bureaucracy or to disgraced methods of simulated activities of self-government. The events of the years 1980 - -1983 are treated as transitional episodes which could only briefly throw the activists off their balance. For they are often characterized by conservatism, backward attitudes and the narrow perspectives of viewing the estate problems with separation from the spirits manifested in the events of recenty years.
Residents self-government in the face of the 1980-1983 events in the opinions of housing estate activists